The Evolving Face of Heart Failure Associated with Elevated Cardio-Metabolic Risk Factors - Dutt, Chaitanya; Chauthaiwale, Vijay; Mohanan, Anookh; Chandra, KumarPrafull; Zambad, Shitalkumar; Gupta, Ram; Parikh, Siralee (IntechOpen, 2012)
None